Best Answer

eqn1 5x - y = -6

eqn2 -x + y = 2

rearrange eqn1 to isolate y

y = -1*(-6-5x)

y = 6+5x

substitute this into eqn2

-x + 6 + 5x = 2

4x + 6 = 2

4x = -4

x = -1

substituting this into eqn1

-5 -y = -6

y = 1

Q: 5x-y equals -6 -x plus y equals 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-2

2+2=4 not 6

Minus 8 plus 6 equals -2.

Bruno mars is hot pooop

DIE

Related questions

No.

3y = 5xy = x + 23y = 5x3(x + 2) = 5x3x + 6 = 5x3x - 3x + 6 = 5x - 3x6 = 2x6/2 = 2x/23 = xy = x + 2 = 3 + 2 = 5Thus, the solution of the set is (3, 5)Check:

2 plus 2 equals 4plus1 equals 5minus 1 equals 4divided by 2 equals 2plus 8 equals 1010 minus 6 equals 4so it all equals to +_____29so its 29 !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

8x-7 plus 2x equals 6 plus 5x plus 2?

Yes?

correct!! 2 plus 2 does equal 4!! yay u!!

-2

2+2=4 not 6

Minus 8 plus 6 equals -2.

14 - 6 + 2 = 6

10 + 2 - 6 = 6

26